Synthesis and Structural Characterization of Diiron Ethanedithiolate Complex [(μ-SCH2)2Fe2(CO)5]2(Ph2PCH2CH2CH2CH2PPh2) Containing Bridging Diphosphine Ligand - Gao, Wei; Sun, De-Mei; Gao, Peng (Asian Journal of Chemistry, 2014)
A diiron ethanedithiolate complex [(μ-SCH2)2Fe2(CO)5]2(Ph2PCH2CH2CH2CH2PPh2) (1) has been prepared and characterized by spectroscopy. The title complex was synthesized by reaction of [(μ-SCH2)2]Fe2(CO)6 (A) with dppb (Ph2PCH2CH2CH2CH2PPh2) in the presence of the decarbonylating agent Me3NO·2H2O in MeCN at room temperature in 66 % yield. The new complex was characterized by IR, 1H NMR, 31P NMR and 13C NMR spectroscopy.